1982
DOI: 10.1128/aac.22.6.1064
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Evaluation of N -Formimidoyl Thienamycin (MK0787) Combined with Amikacin Against Gram-Negative Bacilli and Staphylococcus aureus

Abstract: The in vitro synergistic activity of N-formimidoyl thienamycin and amikacin was determined against gentamicin-resistant enterobacteriaceae, Pseudomonas aeruginosa, and Staphylococcus aureus. N-Formimidoyl thienamycin showed synergism with amikacin against 19 of the gentamicin-resistant strains, 14 of the 49 strains of S. aureus, and only 1 strain of the 46 P. aeruginosa isolates.Thienamycin is a P-lactam antibiotic of novel structure produced by Streptomyces cattleya (4). The activity of this compound is chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
4
1

Year Published

1984
1984
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
1
4
1
Order By: Relevance
“…In contrast to studies reported previously (9,12), we have shown a significant incidence of synergy (45%) when imipenem and amikacin were combined and tested against imipenem-susceptible isolates of P. aeruginosa. These findings would support previous observations of increased rate of killing of P. aeruginosa by the combination of imipenem and amikacin (19).…”
contrasting
confidence: 54%
“…In contrast to studies reported previously (9,12), we have shown a significant incidence of synergy (45%) when imipenem and amikacin were combined and tested against imipenem-susceptible isolates of P. aeruginosa. These findings would support previous observations of increased rate of killing of P. aeruginosa by the combination of imipenem and amikacin (19).…”
contrasting
confidence: 54%
“…However, in this series of studies, investigations of its interactions with other antimicrobial agents are relatively limited. Overall, synergism has been demonstrated in combinations of imipenem with aminoglycosides against enterococci (3, 8, 10, 24) and Listeria monocytogenes (8) and less frequently against staphylococci, enteric gram-negative bacteria, and nonfermentative bacteria (7,11,14,18,19). Conversely, imipenem has shown antagonistic interactions with other ,-lactam antimicrobial agents against Pseudomonas aeruginosa (1,4, 25) and Serratia marcescens (17) and with chloramphenicol against Klebsiella pneumoniae (6).…”
mentioning
confidence: 99%
“…Synergism at clinically attainable concentrations was defined, for the purpose of this study, as the inhibition of growth at concentrations of antibiotics in combination that were no more than one-fourth the initial MIC of each drug and .16 ,ug/ml for amikacin, .8 p.g/ml for netilmicin, . 4 Fig/ml for gentamicin and tobramycin, s8 pLg/ml for cefotaxime, ceftizoxime, imipenem, and Sch 29482, s16 ,ug/ml for cefsulodin and ceftazidime, s64 ,ug/ml for cefpiramide and ceftriaxone, and s32 ,ug/ml for all other ,B-lactams. These concentration breakpoints were based on a review of the pharmacokinetic data in published articles and from pharmaceutical companies and represent levels generally attainable at the midpoint of dosing intervals at intervals and doses that one might use to treat serious infections.…”
mentioning
confidence: 99%
“…All isolates were identified by standard microbiological methods. We evaluated 4 amino-glycoside-p3-lactam pairs were evaluated for synergism (1,680 assays were done). Synergism at clinically attainable concentrations was defined, for the purpose of this study, as the inhibition of growth at concentrations of antibiotics in combination that were no more than one-fourth the initial MIC of each drug and .16 ,ug/ml for amikacin, .8 p.g/ml for netilmicin, .…”
mentioning
confidence: 99%